Perception of Social Science Department Students on the MBKM Campus Teaching Program of FKIP at Lambung Mangkurat University - Huda, Atiqatul; Hastuti, Karunia Puji; Angriani, Parida; Aristin, Nevy Farista; Saputra, Aswin Nur (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2024)
The Independent Learning - Independent Campus (MBKM) is a policy program of the Ministry of Education, Culture, Research and Technology to train students by providing learning experiences outside of higher education in order to provide opportunities for students to hone skills according to their abilities talents and interests with direct practice in the world of work as one of the steps in pursuing a career. The purpose of this study was to analyze the perceptions of students majoring in social science towards the teaching campus program at FKIP in the even semester of the 2022/2023 and 2023/2024 academic years that they attended. The data used are primary data, namely in the form of a questionnaire given to students participating in the teaching campus which is presented through google form and secondary data where student data comes from the Faculty of Teacher Training and Education, Lambung Mangkurat University. The method used in this research is descriptive percentage using Likert scale. The results showed that student perceptions of the MBKM (Independent Learning - Independent Campus) teaching campus program showed an average score of program learning outcomes that were included in the excellent category with a total of 44.21